Evaluation of an e‐book assignment using Fink's Taxonomy of Significant Learning among undergraduate dental hygiene students. Issue 10 (15th June 2020) - Partido, Brian B.; Chartier, Elizabeth; Jewell, Jennifer
Abstract: Context: With significant learning experiences, students undergo positive, substantial, and lasting influences on their personal and professional lives. With grant support from The Ohio State University's Affordable Learning Exchange Program, students created e‐book chapters for a Current Concepts in Dental Hygiene as a significant learning experience. Objective: The purpose of this study was to evaluate the impact of an e‐book chapter creation project on the learning of undergraduate dental hygiene students using Fink's Taxonomy of Significant Learning. Design: Upon IRB exemption, this study involved a mixed‐methods, cross‐sectional research design involving a survey of attitudinal and reflective questions. The data were analyzed using descriptive statistics and thematic analysis. Results: The data from 100% (n = 41) of the dental hygiene students enrolled in the Current Concepts in Dental Hygiene course were analyzed. Most students recognized the alignment of the 6 scaffolded assignments with the 6 domains of Fink's Taxonomy of Significant Learning. Most students agreed the project focused on foundational knowledge (68.8%, n = 27), promoted active learning (73.2%, n = 30), applied to real life problems (63.4%, n = 26), and provided life lessons (56.1%, n = 23). Thematic analysis revealed students appreciated the teamwork involved and the scaffolding of assignments, recognized the challenges of inconsistent feedback and technical issues with the software, and felt that more faculty guidance and technical support would have improved their experiences. Conclusion: Future research should evaluate the impact of using Fink's Taxonomy of Significant Learning with the design of courses or course‐long projects on the education of dental and dental hygiene students.